Transition ability to safe states reduces fear responses to height - Misako Fujino; Masahiko Haruno (Proceedings of the National Academy of Sciences, 2025)
Previous studies on fear extinction have primarily focused on repeated exposure to fear-inducing context without negative consequences. However, it is also possible that an individual can reduce fear responses by predicting that they can transition to a safe environment through their own actions, even if a fear-inducing context appears. Here, by conducting two virtual reality (VR) experiments (Exp 1 and Exp 2) involving height and flight scenarios, we examined whether participants’ fear responses to height decrease after actively experiencing low-altitude VR flight, which allowed them to predict that they would be in a safe state by flying even if they fell from a height. Specifically, participants in the flight group (n = 44 and 46) flew over a city at altitudes below 5 m for 7 min, while participants in the control group (n = 41 and 28) watched a video of a flight group participant’s experience. Before and after the active flight or passive viewing task, both groups walked on a plank while having their skin conductance response (SCR) and subjective fear score (SFS) measured. In both Exp 1 and Exp 2, the active flight group exhibited a greater reduction in both SCR and SFS compared to the control group. Additionally, a multivariate regression of SCR using the questionnaires collected in Exp 2 revealed that the action-dependent safety prediction has a positive contribution to the SCR reduction in the flight group. These results clarified that the ability to transition to safe states by self-actions can reduce physiological and subjective fear responses.